Internacionalização de pequena empresa brasileira de base tecnológica: caso Pipeway Engenharia limitada - Segalis, Gabriel (2012)
This essay aims to verify how the activities developed by Pipeway Engenharia Limitada2 - a service supplier on the oil, gas and energy sector/industry – match the theoretical concepts of the New International Venture Paradigm – NIV (RENNIE,1993; MCDOUGALL et. Al.,1994), during its process of internationalization. The approach assumes significative relevance to the author, since the comprehension of the internationalization process on the Company, which is considered a small business, allows their professional activities to be developed with better comprehension of needs, demands and solutions required for the /small businesses’/company’s internationalization. In order to achieve that purpose, the author has made use of a Single Case Study. This choice may be defined by two reasons: Firstly, it is worth pointing out that , in Brazil, there is not a significant quantity of companies which have similar characteristics with the studied company; Secondly, this method is usually applied when it comes to solving questions such as 'how' and 'why', that is, when the aim is to comprehend individual phenomena. Moreover, it has been necessary to develop a brief study - based on documental and bibliographic analysis – not only to understand the supplier industry evolution on the international market, but also to determine the development and importance of this case as a business development affluence, innovation and support factor.Considering that the analyzed company’s main field is the oil and gas sector, a study based on a national and international scope has been made in order to comprehend this economic sector. Also, apart from other international segments, companies which develop their activities in this area usually face opened and globalized markets, and these characteristics impact significantly on Pipeway. The junction of the first and second analysis has allowed the evaluation of not only the competitive degree, but also other refferences that a company has to follow so as to be considered a New International Venture. Later on – based on case study methodological precepts, data obtained by research and information from interviews with the company´s senior management- a historiographical report of the company´s internationalization process has been elaborated. This work has emphasized events and facts which allow us to prove the adherence or not to the NIV paradigm´s assumptions. Hence, the author has investigated the company´s international evolution according to analysis criteria, which are directly related to NIV paradigm.Actually, this study allowed the statement bound to the conclusion in an empirical manner that Pipeway´s internationalization process responds to NIV´s paradigm in a complete way. One example that may be pointed out is the beginning of internationalization and proven relation between trade income and total revenue. Additionally, some suggestion have been presented for the sake of future research development, enhancement of government programs which support the internationalization process of Small Businesses , as well the author´s professional performance.